Strategi Pengembangan Budaya Literasi Sekolah: Studi Kasus di MIN 6 Tangerang - Wurinda Nur Baiti; Dayu Retno Puspita; Ibrahim Guntur Nuary (Universitas Hamzanwadi, 2026)
Literacy culture is an important aspect of improving the quality of learning and shaping students' character in elementary schools. However, low reading interest and various challenges in implementing the School Literacy Movement (Gerakan Literasi Sekolah [GLS]) remain issues faced by many educational institutions. This study aims to describe the strategies for developing a literacy culture at MIN 6 Tangerang Regency, identify the supporting and inhibiting factors in the implementation of literacy programs, and analyze their impact on students. This research employed a qualitative approach with a case study design. The research participants consisted of the principal, vice principal for curriculum affairs, classroom teachers, and students selected through purposive sampling. Data were collected through observation, interviews, and documentation, and then analyzed through data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and time triangulation. The findings reveal that the literacy culture development strategy at MIN 6 Tangerang Regency is implemented through the stages of habituation, development, and learning. The habituation stage includes 15-minute reading activities before lessons, the Wednesday Reading Movement (GERCA), and the utilization of reading corners. The development stage is carried out through various literacy activities, such as storytelling, poetry recitation, speech contests, pildacil (Islamic preaching for children), and writing activities, while the learning stage integrates literacy into the teaching and learning process. Supporting factors include the principal’s commitment, teacher involvement, parental support, and the availability of literacy facilities. Meanwhile, inhibiting factors consist of limited reading materials, excessive use of digital media, and differences in students’ reading abilities. The literacy program positively contributes to the improvement of students’ reading interest, learning motivation, discipline, responsibility, and communication skills.